Current paediatric auditory processing disorder assessment and management practices implemented by speech-language therapists working in private pratices in Johannesburg, South Africa - Lewis, Liane T (My University, 2015)
The number of children being diagnosed with Auditory Processing Disorder (APD) is increasing and the lack of standardized assessment and management across speechlanguage therapists (SLT) in South Africa, as well as the lack of general consensus in defining and managing this disorder globally, leaves open the possibility of adverse effects on a child’s education, selfesteem and future (Musiek & Chermak, 2007). Due to this lack of consensus in defining and implementing protocols in South Africa, assessment and management of children with APD is not being optimized. The following research aimed to investigate the practices used by SLTs regarding the assessment and management of children with APDs in Johannesburg, South Africa. In this qualitative, explorative study, data collection comprised of interviews with ten English speaking SLTs that worked within the private practice setting, with a minimum of one year’s clinical experience in the area of APD assessment and management practices. Thematic analysis of the information did cast light on patterns and procedures being used across SLTs; to provide insight into the current assessment and management practices of SLTs working within a private practice setting in Johannesburg, so as to inform and guide the development of more standardized, culturally appropriate assessment and management practices and tools in South Africa. This research identified the paucity of knowledge regarding the APD practices being implemented by SLTs, internationally as well as within South Africa. Highlighted themes included that most SLTs obtained their APD assessment and management practical knowledge by observing other practicing SLTs and implementing selflearning, as there was little or no formal training on the topic of APD readily available on the completion of their degree. Another observed theme highlighted that the tools used for the APD assessment and management were not always appropriate for the South African population. There was also a lack of consensus regarding the referral pathway for a child presenting with APD. This research study provides insight into the assessment and management practices working within the private healthcare sector in Johannesburg, South Africa, for future research to be built upon. Key Words: paediatric auditory processing disorder, universal guidelines, assessment, management, speechlanguage therapists.
Department of Speech Pathology and Audiology School of Human and Community Development Faculty of Humanities University of the Witwatersrand November 2014